The Influence of Artificial Intelligence on Vietnam’s Higher Education in the Contemporary Era - Long, Tran Thai; Trang, Pham Thi; Bien, Tao Ngoc; Cuong, Ton Quang (VNU Journal of Science: Education Research; Vol 42 No 1DO - 10.25073/2588-1159/vnuer.5276, 2026)
In the current era, artificial intelligence (AI) plays an increasingly important role in shaping the technological revolution and changing the manufacturing and education dynamics. Moreover, Artificial Intelligence in Education (AIEd) stands out as a field that focuses primarily on applying advances in artificial intelligence to capture and optimize the performance of the learning process while making an essential contribution to creating an effective and progressive learning environment. The context of applying information technology and digital transformation in education and training in Vietnam, especially at the higher education level, has been studied in detail and analyzed thoroughly. From this information, the study focused on the orientation of applying artificial intelligence (AI) in the higher education sector, describing in detail the difficulties and challenges arising from this process. In particular, the comprehensive study highlights the potential prospects of integrating artificial intelligence (AI) into the teaching process at the university level in Vietnam in the future. Finally, by synthesizing the information obtained, the study concludes and makes specific recommendations on the future direction of artificial intelligence in higher education in the context of current digital transformation.